2014
DOI: 10.2174/1567202611666140530130327
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Albumin to Creatinine Ratio as Potential Biomarker for Cerebral Microvascular Disease

Abstract: Elevated urinary albumin to creatinine ratio (ACR) and white matter hyperintensity (WMH) volume seen on brain MRI are measures of microvascular disease which may have shared susceptibility to metabolic and vascular insults. We hypothesized that elevated ACR may be useful as inexpensive biomarker to predict presence of cerebral microvascular disease. We assessed the association between ACR at study entry and subsequent WMH volume. We evaluated pulse pressure, mean arterial pressure, hypertension duration, waist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Previous epidemiological studies have shown that elevated urinary albumin is associated with larger WMHV, [12][13][14][15][16] which is consistent with the findings of the present study. This study showed that increased urinary albumin, within variables were assessed by means of a cross-sectional design, we could not definitively establish causality among them.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous epidemiological studies have shown that elevated urinary albumin is associated with larger WMHV, [12][13][14][15][16] which is consistent with the findings of the present study. This study showed that increased urinary albumin, within variables were assessed by means of a cross-sectional design, we could not definitively establish causality among them.…”
Section: Discussionsupporting
confidence: 93%
“…Several cross-sectional observational studies conducted in Western countries have reported that elevated urinary albumin levels are significantly associated with larger WMH volumes, which were measured quantitatively by automatic techniques. [12][13][14][15] Only study has used automatic quantitative evaluation of WMH in Asian populations with different genetic and lifestyle backgrounds. 16 Moreover, several epidemiological studies have examined the association of albuminuria with WMH enlargement in general Asian populations.…”
mentioning
confidence: 99%
“…A cross‐sectional study of 568 individuals with hypertension without a history of stroke found that 1 SD increase in ACR was associated with higher odds for deep and infratentorial CMBs (OR = 2.03, 95% CI = 1.41–4.31), but no association was found for lobar CMBs . A population‐based study found an association between baseline ACR and WMH volume after 7 years ( β = 0.039, P = .05) and a stronger association when ACR and WMH were concurrently assessed ( β = 0.073, P < .001). An analysis of the total burden of cerebral SVD (WMHs, LIs, CMBs, EPVSs) in 210 individuals with acute stroke found greater burden in subjects with proteinuria (OR = 2.15, 95% CI = 1.16–3.98) …”
Section: Resultsmentioning
confidence: 99%
“…6 The ocular fundus photographic changes and 24-h urine protein in T2DM patients might provide a clue of microangiopathy. [7][8][9][10] In this study, we sought to investigate the correlation between microangiopathy and BMD in postmenopausal women with T2DM and age-matched male patients using ocular fundus photographic changes and 24-h urine protein as surrogate microangiopathy markers.…”
Section: Microangiopathy Is Associated With Bone Loss In Female Type mentioning
confidence: 99%